An Ambit Stochastic Approach to Pricing Electricity Forward Contracts: The Case of the German Energy Market. (27th October 2015) - Di Persio, Luca; Perin, Isacco
Abstract : We propose an ambit stochastic model to study the electricity forward prices. We provide a detailed analysis of the probabilistic properties of such model, discussing the related martingale conditions and deriving concrete implementation of it for the related underlying spot price. The latter is obtained from the forward model through a limiting argument. Furthermore, we show, also providing a concrete example, that a proper specification of these models is able to effectively forecast prices of forward contracts written on the European Energy Exchange (EEX) AG, or German Energy Exchange, market.